A Circularly Polarized Miniaturized Patch Array Using Combination of Circle and Rectangular Lines in the Sequential Phase Feed Structure - Mohammad Hosein Rasekhmanesh; Pejman Mohammadi; Asrin Piroutiniya (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A sequential phase (SP) feed array antenna circularly polarized (CP) with 2×2 patch array is presented. The feeding network consist of two piece of circle that are filled with rectangular lines and have four arms that make 900 phase difference for the corner truncated elements which are connected to the feeding network. The combination of circle and rectangular lines reduces the size of the feeding network and thus, the overall size of the antenna with good characteristics to prove the antenna performance, the prototype antennas built and the results come in the form of: the measured 10 dB impedance bandwidth is 0.5 GHz (3.45 - 3.95 GHz), and the measured 3-dB AR bandwidth is 0.3 GHz (3.45 - 3.75 GHz).